2012
DOI: 10.1371/journal.pone.0051183
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss and Cytokines Levels in an Experimental Model of Psoriasis

Abstract: Up to 80% of people develop a cutaneous condition closely connected to their exposure to stressful life events. Psoriasis is a chronic recurrent inflammatory skin disorder with multifactorial etiology, including genetic background, environmental factors, and immune system disturbances with a strong cytokine component. Moreover, psoriasis is variably associated with sleep disturbance and sleep deprivation. This study evaluated the influence of sleep loss in the context of an animal model of psoriasis by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 68 publications
7
87
0
2
Order By: Relevance
“…In an experimental model of psoriasis, it has been suggested that sleep disturbance plays a dominant role in the exacerbation of psoriasis via the dysregulation of the immune mechanisms in the epidermal barrier. Thus, sleep disturbance should be considered as a risk factor for the development of psoriasis [14]. Our study presents additional confirmation that besides sleep disturbances, patients with psoriasis have substantially impaired sleep quality compared with general healthy people [11,12,15].…”
Section: Discussionsupporting
confidence: 69%
“…In an experimental model of psoriasis, it has been suggested that sleep disturbance plays a dominant role in the exacerbation of psoriasis via the dysregulation of the immune mechanisms in the epidermal barrier. Thus, sleep disturbance should be considered as a risk factor for the development of psoriasis [14]. Our study presents additional confirmation that besides sleep disturbances, patients with psoriasis have substantially impaired sleep quality compared with general healthy people [11,12,15].…”
Section: Discussionsupporting
confidence: 69%
“…A protocol of 5 days of sleep restriction induced a higher production of IL-6, IL-1b and IL-17 in healthy male volunteers [73]. In support of this idea, Hirotsu and collaborators [35] reported that sleep deprivation increased the activity of kallikreins-5 and 7, which are polypeptides with proteolytic activity associated with animal model of psoriasis. Furthermore, concentrations of the proinflammatory cytokines IL-1b, IL-6, and IL-12 increased while IL-10 decreased, indicating that sleep loss is a risk factor for psoriasis.…”
Section: Sleep: Neglected By Modern Routinementioning
confidence: 87%
“…50,51 Once activated, keratinocytes produce IL-6 and IL-8, 52,53 which sustain inflammation and promote abnormal keratinocyte proliferation. 40 IL-6 induces an acute inflammatory reaction and also supports the activation of lymphocytes, which may increase serum levels of IL-6 in an inflammation-promoting positive feedback loop, 54 while IL-8 provides a strong chemotactic signal resulting in neutrophil and T lymphocyte recruitment to the skin lesion. 55 Thus, these cytokines are a hallmark in the network of cytokines that characterize psoriasis, 52 and together with constant proliferation of keratinocytes contribute to the perpetuation of the disease.…”
Section: Discussionmentioning
confidence: 99%